2013
DOI: 10.1158/0008-5472.sabcs13-s2-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S2-03: Early follow up of a randomized trial evaluating resection of the primary breast tumor in women presenting with de novo stage IV breast cancer; Turkish study (protocol MF07-01)

Abstract: Introduction: Previous reports of carefully selected patients presenting with stage IV breast cancer (BC) suggest that surgery on the primary tumor may result in improved survival, but this remains unproven. The MF07-01 trial is a phase III randomized controlled trial of BC women with distant metastases at presentation who receive loco-regional (LR) treatment for intact primary tumor compared with those who do not receive such treatment. Aim: The primary objective of the trial is to compare over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…In the study from the Turkish Federation of Societies for Breast Diseases Soran et al, suggested that patients with isolated bone metastases may benefit from surgery, whereas such an approach was even detrimental in patients with visceral involvement. 36,37 The results suggest surgery was not of benefit in the majority of patients, and in fact may lead to worse outcome as reported in the TATA study. A subgroup with isolated or bone only metastasis may benefit from surgical excision of breast primary tumor, confirming the observations of the retrospective series from British Columbia, one of the published population-based analyses mentioned above.…”
Section: Reviewmentioning
confidence: 72%
“…In the study from the Turkish Federation of Societies for Breast Diseases Soran et al, suggested that patients with isolated bone metastases may benefit from surgery, whereas such an approach was even detrimental in patients with visceral involvement. 36,37 The results suggest surgery was not of benefit in the majority of patients, and in fact may lead to worse outcome as reported in the TATA study. A subgroup with isolated or bone only metastasis may benefit from surgical excision of breast primary tumor, confirming the observations of the retrospective series from British Columbia, one of the published population-based analyses mentioned above.…”
Section: Reviewmentioning
confidence: 72%
“…A randomized clinical trial from Turkey, with more than 20 months of follow-up, suggested that patients with solitary bone metastases had significantly improved survival following complete excision of the primary breast tumor and regional nodes. 12 However, interpretation of this work is limited by small patient numbers and lack of a confirmatory biopsy of the presumptive metastatic site. A retrospective study of 300 women found a survival advantage for patients undergoing breast surgery who had bone-only metastases.…”
mentioning
confidence: 97%
“…Two randomized trials, here to presented only in abstract form, failed to show an overall survival benefit to primary disease-site surgery. 12,13 Prospectively enrolled registries may also further delineate the role of surgery in metastatic breast cancer. 14 Current guidelines for the management of stage IV breast cancer consider this a systemic disease and generally reserve primary site treatment for palliation of local symptoms.…”
mentioning
confidence: 99%
“…The second important prospective randomized study presented in SABCS was performed by the Turkish Federation of Breast Disease Societies with a title of "Early follow up of a randomized trial evaluating resection of the primary breast tumor in women presenting with de novo stage IV breast cancer; Turkish study (protocol MF07-01)" (4). This is the first time a study performed in Turkey has been orally presented in SABCS.…”
Section: Discussionmentioning
confidence: 99%